A New Approach to the Design of Helical Shape Memory Alloy Spring Actuators. (26th December 2011) - Khan, Esuff; Srinivasan, Sivakumar M.
Abstract : Shape memory alloys (SMAs) are smart materials that have the ability to recover their original shape by eliminating residual deformations, when subjected to adequate temperature rise (Shape memory effect). This special behavior attracts the use of SMAs as efficient stroke/force actuators. Most of the engineering applications require helical springs as actuators and proper design of SMA helical spring actuators is very important. In the traditional design approach of SMA spring (Waram, 1993), only strain between linear zones was considered in order to simplify the design and to improve the fatigue life. Only modulus difference between high-temperature and low-temperature phase was utilized, and the transformation strain was not considered as the total transformation strain will be more and will degrade the performance of actuator. In the present design, we have shown that transformation strain can be restricted by using hard stops and the partial transformation strain can be used to improving the capacity of SMA spring actuator. A comparison of the traditional design approach of SMA spring and the proposed design procedure has been made to give an idea of its effect on the design and the related parameters.